Energy and economic evaluation of three generations of anaerobic reactors for starch wastewater treatment. Issue 1 (1st January 2019) - He, Huihui; Ji, Xiaowen; Xie, Xianchuan; Ding, Xinchun; Wang, Fang; Ding, Jue; Hai, Zibin; Tang, Rong
ABSTRACT: Three anaerobic reactors for treating starch wastewater as the Anaerobic Digester (AD), Up-flow Anaerobic Sludge Blanket (UASB) reactor, and Internal Circulation (IC) reactor, were assessed in terms of energy supply and economic factors pertaining to biogas production. For all three reactors, more than 90% of heat loss was derived from the substrate heating loss. When the Chemical Oxygen Demand (COD) of wastewater exceeded 15, 000mg/L, the UASB and IC reactors produced excess energy and achieved an economic surplus throughout the year. The UASB and IC reactors reached energy equilibrium throughout the year when the influent COD was 11, 195.44mg/L, and 9, 844.67mg/L, respectively. The economic equilibrium of the UASB and IC reactors was achieved for influent COD of 12, 984mg/L and 11, 561mg/L, respectively. The energy and economic equilibria of the AD could not be achieved throughout the year with influent COD concentrations ranging from 5, 000mg/L to 20, 000mg/L.